Writings of the common in Latin American digital works: the Eugenio Tisselli case - Gordillo Lizana, Emilio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This article proposes to approach Eugenio Tisselli’s work from the politics of the commons in order to recognize a series of subversive practices that involve Latin American agencies and cosmotechnics in the context of a digital world increasingly normativized by surveillance capitalism, neo-extractivism and the primacy of exchange value. These deployments of reappropriation of common goods contained in language dispute conceptions of alternative times to capital through collaborative exercises of production, promotion of use value over exchange value, transformation and denaturalization of modern languages of dispossession.